LEVERAGE DYNAMICS: THE ROLE OF PROFITABILITY AND FIRM SIZE IN SHAPING FIRM VALUE - Chang, Evelyn Victoria; Wirianata, Henny (International Journal of Application on Economics and Business, 2025)
This study examines the influence of leverage on firm value with profitability and firm size acting as influencing variables in non-cyclical sector companies listed on the Indonesia’s Capital Market between 2020 - 2023. This study uses 188 observation data from 47 companies selected through the purposive sampling. Tobin’s Q is utilized to calculate firm value, while leverage is evaluated using the ratio of debt to total assets. The Return on Assets (ROA) ratio measures profitability, whereas the natural logarithm of total assets is employed to assess firm size. Multivariate linear regression analysis in the first model without moderation shows that leverage and profitability have a considerable favorable impact on firm value. In contrast, firm size has a considerable adverse impact. In the second model, profitability was tested as a influencing variable in the link between leverage and firm value, but no significant moderating effect was found. The same thing is also found in the third model, where firm size as a moderating variable does not have a meaningful impact on the leverage-firm value connection. The study’s result demonstrates that although leverage, profitability, and company size impact firm value directly, profitability and firm size as moderating variables are not strong enough to affect the dynamics between leverage and firm value. Therefore, it is recommended that company management focus more on optimizing financial structure and operational efficiency without relying too much on company size growth to increase firm value.